Cilgavimab/Tixagevimab as alternative therapeutic approach for BA.2 infections - Dichtl, Stefanie; Zaderer, Viktoria; Kozubowski, Viktoria; Abd El Halim, Hussam; Lafon, Eliott; Lanser, Lukas; Weiss, Günter; Lass-Flörl, Cornelia; Wilflingseder, Doris; Posch, Wilfried (Frontiers in Medicine, 2022)
Objectives: The identification of the SARS-CoV-2 Omicron variants BA.1 and BA.2 immediately raised concerns about the efficacy of currently used monoclonal antibody therapies. Here, we analyzed the activity of Sotrovimab and Regdanvimab, which are used in clinics for treatment of moderate to severe SARS-CoV-2 infections, and Cilgavimab/Tixagevimab, which are approved for prophylactic use, against BA.1 and BA.2 in a 3D model of primary human bronchial epithelial cells. Methods: Primary human airway epithelia cells in a 3D tissue model were infected with clinical isolates of SARS-CoV-2 Delta, BA.1 or BA.2. To mimic the therapeutic use of mAbs, we added Regdanvimab, Sotrovimab or Cilgavimab/Tixagevimab 6h after infection. In order to mirror the prophylactic use of Cilgavimab/Tixagevimab, we added this compound 6h prior to infection to the fully differentiated, pseudostratified epithelia cultured in air-liquid interphase (ALI). Results: We observed that Sotrovimab, but not Regdanvimab, is active against BA.1; however, both antibodies lose their efficacy against BA.2. In contrast, we found that BA.2 was sensitive to neutralization by the approved prophylactic administration and the therapeutic use, which is not yet permitted, of Cilgavimab/Tixagevimab. Conclusion: Importantly, while the use of Tixagevimab/Cilgavimab is effective in controlling BA.2 but not BA.1 infection, monoclonal antibodies with efficacy against BA.1 are ineffective to reduce BA.2 virus replication in a human lung model. Our data may have implications on the variant specific clinical use of monoclonal antibodies.